Purine base transport in nit-2 mutants of Neurospora crassa. - Pendyala, L (1978)
The nit-2 mutants possess general purine transport activity. Reduced hypoxanthine uptake in germinated conidia of these mutants may be a consequence of their defective purine metabolism.